STRUKTUR GERAK TARI JEPIN LANGKAH GERSIK PANTAI KOTA PONTIANAK KALIMANTAN BARAT - Slamet, Deni; Ismunandar, Ismunandar (Universitas Tanjungpura, 2022)
The background of this research is because of the researchers' concerns about the authenticity of the various movements of the Jepin Step Gersik Pantai Dance, which in the future does not rule out changes. Therefore the researchers described and documented the Jepin Step Gersik Pantai Dance in the form of writing, pictures and videos. The method in this study is a descriptive method with a qualitative research form and a choreographic approach. Data collection techniques in the form of observation, interviews, and documentation studies. The data validity testing technique used is the extension of observations and triangulation of sources. Based on the data analysis, it was concluded that the movement structure of the Jepin dance step Gersik Pantai Pontianak City, West Kalimantan is as follows: there are 3 variations consisting of coastal steps, Nyusor Arus, Nyusor Waves which are composed of 9 sub-ranges, namely Serimpik Steps with Hooks, Steps with Oblique Feet. , Body Leaning Steps, Bunga Lampai Bunga Serpai Steps, Hanging Pull Steps, Pencak Punch Steps, Steps to Avoid People's Punches, Rope Weaving Steps, and Kembang Rifle Steps. The Jepin Step Gersik Pantai dance consists of 154 motion motifs, 37 motion phrases, 7 motion sentences, and 1 movement cluster which forms a complete movement unit in the Jepin Step Gersik Pantai dance